EXAMINING THE FACTORS THAT LEAD TO THE DELAYED GROWTH OF REVERSE MORTGAGES - Khare, Sachin; Khan, M.A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Those who are 60 years of age or older are eligible for a Reverse Mortgage. Homeowners may access the equity in their fixed assets and put it to use in their golden years using this loan product. By using a Reverse Mortgage, homeowners are able to enjoy the benefits of their property throughout their lifetime without having to return any kind of debt. The worth of their residence is intertwined with their network, and it provides the income necessary for subsistence. Aims and Objectives: From the viewpoints of the borrowers (the elderly) and the lenders (the banks and other financial organizations), this research aims to identify the variables that influence the efficacy or lack thereof of reverse mortgages. Methodology: Books, journals, previous publications, and researcher interviews will make up the bulk of the secondary data set for this qualitative study. Findings and Discussion: Examining the maintenance risk that borrowers face in Reverse Mortgages from both the lender's and the borrower's point of view is the primary objective of the present research. Researchers were able to successfully categorize and identify variation from both an internal and an external viewpoint in the research. Conclusion: In order to reach a successful conclusion, it takes into account the Reverse Mortgage and the numerous factors that impact both borrowers and lenders when taking out a home loan, all while effectively managing their risk. The findings are based on literature and academic reviews.